Staphylococcus Hominis Improving the Efficiency of Cephalexin in Treating of Resistant Staphylococcus Hominies - Al-asadi, Othaim Razzaq Faliyh; Al Shamry, Oras Saleh Hassan; Al daami, Alaa Alaa Abdul Hussein Karim (Journal of Science in Medicine and Life, 2025)
Objective: The current study aimed to manufacture a hybrid nano-antibiotic from the antibiotic Cephalexin to enhance its efficacy against the antibiotic-resistant bacteria Staphylococcus hominis. Methods: Direct ion exchange between the zinc oxide (ZnO) and cephalexin (CEPH) layers was used to create a hybrid antibiotic known as Cephalexin-ZnO. Atomic force microscopy (AFM), scanning electron microscopy (SEM), FT-IR spectroscopy, X-ray diffraction (XRD), and CHNS elemental analysis were used to identify the novel nanobiotic. The study examined the hybrid nanocellulose cephalexin's antibacterial activity against Staphylococcus hominis bacteria that were isolated from the blood of a patient who had been diagnosed with sepsis using the Vitek 2 device. Results: The sensitivity test results in the Vitek 2 device for the bacteria Staphylococcus hominis showed that it is resistant to the antibiotic Cephalexin. FTIR infrared spectroscopy, XRD X-ray diffraction, AFM atomic force microscopy, and SEM scanning electron microscopy indicated the successful loading of this antibiotic into ZnO layers, with a loading percentage reaching 36.88% according to CHNS elemental analysis results. Additionally, With inhibition zone diameters of 0, 0, 2.63, 12.1, 18.67, and 26.71 mm against the used bacteria at the following concentrations (0, 10, 20, 40, 80, 160) mg/ml, the hybrid nanocomposite demonstrated superior inhibitory activity against the resistant bacteria in comparison to the free antibiotic. For the same concentrations, the inhibition zone diameters for the free antibiotic were 0, 0, 0, 10.3, 15.04, and 21.58 mm. Conclusion: It can be concluded from the current study that the antibiotic Cephalexin was successfully loaded into zinc oxide layers and a hybrid nanocomposite was fabricated, which has been shown to improve its antibacterial efficacy against resistant bacteria.